Perlindungan Hukum terhadap Pemegang Hak Cipta Atas Penggunaan Logo Perguruan Tinggi Universitas Teknologi Sumbawa pada Penjualan Merchandise oleh PT. Olat Maras Teknologi di Sumbawa Nusa Tenggara Barat - Nurul Azizah; Aloysius Sukardan; Orpa J. Nubatonis (LPPM Universitas Sains dan Teknologi Komputer, 2024)
The research objectives are (1) To determine the legal protection of copyright holders for the use of the Sumbawa University of Technology logo in the sale of merchandise by PT. Olat Maras Technology in Sumbawa, West Nusa Tenggara. (2) To find out the legal consequences for business actors who sell merchandise using university logos without permission. The benefit of research is to increase information to the public in general and especially to merchandise business actors, the importance of having permission to use a logo. The method used in this research is the empirical legal method. The results of the research show that: (1) Copyright law protection for the community and students at Sumbawa University of Technology is moderate, because their understanding of the existence of copyright law regarding logos is only limited to discussion and they still order merchandise even though they don't know about the legality of the use of the logo used in making it. merchandise. (2) There are legal consequences for business actors who sell merchandise using university logos without permission. These include sales restrictions and product withdrawals, termination of business activities, legal sanctions, civil lawsuits and revocation of business permits. The conclusions in this research are (1) The legal protection of the Sumbawa University of Technology in the use of copyright for making merchandise by PT Olat Maras Teknologi Sumbawa is categorized as moderate, because the students of the Sumbawa University of Technology only ask questions without considering the goods they will buy. (2) legal consequences for business actors who sell merchandise using university logos without permission, namely termination of business activities. The author's suggestion is that Sumbawa University of Technology must immediately take further action to address the issue of permission to use the university's logo on merchandise produced by PT Olat Maras Teknologi. This could include further negotiations between the College and PT Olat Maras Teknologi to regulate the legal use of the College logo.